Unpacking Name-Based Race Discrimination - Martin Abel; Rulof Burger (Institute of Labor Economics (IZA), 2023)
We investigate the extent and underlying mechanisms of how race beliefs associated with applicants' names affect hiring decisions. Using nationally representative data, we find widespread beliefs that people with names perceived to be Black possess lower levels of education, productivity and noncognitive skills. Notably, this race penalty persists when considering only variation in race perception for the same name and when omitting distinctly Black names. Conducting an incentivized hiring experiment with real worker data, we find that participants are 30 percentage points (pp) more likely to hire workers perceived to be white compared to Black. Controlling for productivity and noncognitive skills beliefs reduces this racial gap to 21 pp and 20 pp, respectively. Results indicate that race serves as a decision heuristic as employers make faster decisions and display more certainty when perceived race differences between candidates are large. Moreover, the race gap in hiring increases by 25% when employers are forced to make quick decisions. Estimates from a structural drift-diffusion model quantify the effect of beliefs and show that employers differ both in their usage of racial heuristics and inclination to override these heuristics when given sufficient decision time.
Keywords: J50; J70; 330; race discrimination; hiring discrimination; name associations